PENGARUH TINGKAT INFLASI, INVESTASI DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DI BEBERAPA NEGARA ASIA TENGGARA - Pitri, Aulia; Murtala, Murtala; Abbas, Tarmizi; Saharuddin, Saharuddin (LPPM UNIMAL, 2024)
The aim of this research is to analyze the influence of inflation, investment and unemployment levels on economic growth in several Southeast Asian countries. The data analysis method used in research with the ARDL model studied from each country is 26 years starting from 1996-2021. The research results show that the inflation rate in the short term has a negative and significant influence on economic growth. Meanwhile, in the long term it also has a negative influence and is followed by a significant level. Investment has a positive and significant impact on economic growth in the short and long term. Unemployment in the short and long term has a positive and significant influence on economic growth.